A new species of Sphaeronemoura (Plecoptera: Nemouridae) from Henan Province of China, with additions to generic characters of the female and larva - Li, Weihai; Murányi, Dávid; Yang, Ding (Zootaxa, 2014)
A new species of the genus Sphaeronemoura (Plecoptera: Nemouridae: Amphinemurinae), S. separata sp. n. is described from the male, female, and larvae collected in Henan Province of China. The internal genitalia of the female adult is described for the first time for the genus, and additional generic characters for the larva are also given. The known distributions of all Sphaeronemoura species is presented.